Penyuluhan Pengaruh Gadget Terhadap Kualitas Tidur Remaja Dewasa di Gereja Pantekosta Tabernakel - Sihombing, Rombadi Yuliana; Sitohang, Ricky Rich; Situmeang, Ivonne Ruth Vitamaya Oishi; Situmorang, Novrina; Sinaga, Inda M. (Universitas Methodist Indonesia, 2024)
Gadgets are modern technology developed with various applications and can provide various media news, social networks, and even entertainment. With the development of technology, gadgets have become commonplace among young people, so the younger generation needs to use gadgets every day. The time of gadget use, duration, and high levels of gadget use at night are one of the factors that influence sleep quality in teenagers. This counseling aims to provide information to help investigate the impact of gadget use on sleep quality among young adults at the Congregational Tabernacle Pentecostal Church Jl. Panci, Medan City.